Respuesta :
Answer:
r = ( q -16)/6
Step-by-step explanation:
In order to rearrange the equation so that r is the independent variable is the same thing as making r the subject of the formula from the given expression
q-10= 6(r+1)
we say,
q - 10 = 6r + 6 ( by using 6 to open the bracket)
we are going to collect the like terms
q- 6r = 6 + 10
q- 6r = 16
q = 16 + 6r
q-16 = 6r
divide both sides by the coefficient of r which is 6
(q-16)/6 = 6r/6
r = ( q -16)/6
Answer:
q = 6r + 16
Step-by-step explanation:
I got this from Khan Academy.
Hope this helps! :)